Comparative techno-economic study of solar energy integrated hydrogen supply pathways for hydrogen refueling stations in China. (1st November 2020) - Gu, Yu; Chen, Qianqian; Xue, Junli; Tang, Zhiyong; Sun, Yuhan; Wu, Qing
Graphical abstract: Highlights: Renewable energy integrated cross-regional hydrogen supply route is proposed. Economic, energy and environmental performance, focusing on hydrogen production and provision. A methodology for analyzing hydrogen supply routes in production, delivery and refueling stage. Abstract: To decarbonize transportation sector, one of the most promising solution is using green hydrogen as an alternative transport fuel to gasoline and diesel. For countries with uneven distribution of renewable energy, it is necessary to evaluate both cross-regional and on-site green hydrogen supply pathways. The goal of this paper is to identify the economic, energy and environmental aspects of potential solar energy integrated green hydrogen supply routes including cross-regional and on-site options for hydrogen refueling stations in China. Four green hydrogen supply routes are proposed in our study: 1) northwest solar power integrated methanol production as hydrogen carrier coupled with cross-regional delivery to hydrogen refueling station for onsite hydrogen production pathway (Route I), 2) northwest solar power integrated hydrogen production coupled with gas H2 cross-regional delivery pathway (Route II), 3) northwest solar power integrated hydrogen production coupled with liquid H2 cross-regional delivery pathway (Route III) and 4) on-site solar energy -powered hydrogen refueling station (Route IV). The results indicate that solar energy integrated hydrogen supply pathways have remarkable CO2 emission reduction effect. Route I, Route II, Route III and Route IV can reduce CO2 emission by 83%, 59%, 96%, and more than 99% respectively, compared with the conventional coal gasification for hydrogen production coupled with gas H2 delivery to nearby fueling station pathway (coal-H2 delivery). In term of energy consumption, Route III and Route IV show advantage in energy efficiency, which consumes 27% and 38% less energy compared with coal-H2 delivery, respectively. In economic aspect, the four routes are not competitive with conventional coal-H2 delivery, but from the perspective of green hydrogen supply, Route I and Route III are economically competitive compared with on-site solar energy-powered hydrogen refueling station (Route IV). If considering carbon tax in 2030 reported by World Bank, Route I will have potential to be economically competitive with coal-H2 delivery. Route III is also expected to be economically feasible as the solar energy electricity price and liquefaction cost further decline.